2019
DOI: 10.4081/reumatismo.2019.1188
|View full text |Cite
|
Sign up to set email alerts
|

The Italian Society for Rheumatology clinical practice guidelines for the diagnosis and management of knee, hip and hand osteoarthritis

Abstract: Osteoarthritis (OA) is the most common musculoskeletal disease leading to functional decline and loss in quality of life. Knees, hands and hips are frequently affected joints with a relevant clinical and socio-economic burden. An evidence-based approach to OA management is essential in order to improve patients’ health and to decrease social burdens. Since new international clinical practice guidelines (CPGs) focused on diagnosis or pharmacological/non-pharmacological treatment have become available in the las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
62
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(68 citation statements)
references
References 37 publications
(38 reference statements)
1
62
0
4
Order By: Relevance
“…OA has been recognized as a major musculoskeletal disease [ 13 ]. The management of mild to moderate OA comprises multidisciplinary interventions, including pain medications and nonpharmacological treatments; however, for end-stage OA, total joint replacement is recommended [ 14 ]. Several recent studies have indicated physical activity and nutrition as nonpharmacological and preventive treatments for OA and sarcopenia [ 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…OA has been recognized as a major musculoskeletal disease [ 13 ]. The management of mild to moderate OA comprises multidisciplinary interventions, including pain medications and nonpharmacological treatments; however, for end-stage OA, total joint replacement is recommended [ 14 ]. Several recent studies have indicated physical activity and nutrition as nonpharmacological and preventive treatments for OA and sarcopenia [ 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Total knee arthroplasty is the main treatment method for patients with knee joint disease who are ineffective after various conservative treatments. Among them, degenerative osteoarthrosis of the knee joint is the most common joint diseases [25]. After patients undergo total knee arthroplasty, joint pain can usually be signi cantly improved, and local deformities can be effectively corrected.…”
Section: Discussionmentioning
confidence: 99%
“…Costo COX-2 = ciclossigenasi-2; FANS = farmaci antinfiammatori non steroidei; OA = osteoartrite metà dei pazienti considerati sia sottoposta a un incremento della posologia/die iniziale. Dall'analisi così realizzata emerge come il costo di gestione appropriata di un paziente affetto da OA, indipendentemente dal sito colpito, considerando i costi delle Liste di trasparenza AIFA e delle alternative farmacologiche, le giornate medie di trattamento e le posologie indicate dal panel di clinici esperti sulla base delle Linee Guida nazionali e internazionali (10), risulta essere pari a €77,79. In particolare, il paracetamolo è il farmaco associato al costo di gestione più basso (€0,35), mentre i FANS sono le alternative associate all'assorbimento di risorse maggiore (€28,31).…”
Section: Mesiunclassified